CHRONIC OBSTRUCTIVE PULMONARY DISEASE, DIAGNOSIS AND TREATMENT - IGN Paramartha Wijaya Putra; I Dewa Made Artika (E-Jurnal Medika Udayana, 2013)
Chronic obstructive pulmonary disease (COPD) is one of a group non communicable diseases that public health has been an issues in Indonesia. At the 2007 in United State, COPD is the third leading cause of death. Smoking habit is a major cause COPD. Symptoms and sign were generally nonspecific. The provision of therapy that late can provide the impact of death. Spyrometry needed for clinical diagnosis COPD. Comparison FEV1/FVC <0,70 after bronchodilator medication can diagnose COPD. Bronchodilator medication is a first line treatment for COPD. Any medicine must specific against each patient, because symptoms and severity of limitations air flow affected by many factors.